Alternative microexon splicing code for a four-amino acid peptide of PTPRD governs behavioral development - Ayako Imai; Hironori Izumi; Nagomi Ito; Hina Ogiso; Yuki Kitajima; Shuhei Kawase; Mizuki Sendo; Kenji Azechi; Toshihide Tabata; Yumie Koshidaka; Shuya Fukai; Keizo Takao; et al. (Proceedings of the National Academy of Sciences, 2026)
Microexons of 3 to 27 nucleotides selectively regulated in the vertebrate nervous system have attracted attention as new elements for modifying the function of neuronal proteins. Protein tyrosine phosphatase δ (PTPRD) is one of presynaptic hubs for neuronal synaptic organization. Alternative splicing (AS) of three microexons, meA3, meA6, and meB, encoding 3, 6, and 4 amino acid-peptides, respectively, imparts structural diversity to PTPRD, due to which the resulting eight splice variants exhibit distinct synaptogenic properties. However, the regulatory mechanisms of AS and physiological significance of the AS code for Ptprd gene remain largely unknown. Here, we report the AS of the three microexons is genetically regulated to generate spatiotemporally distinct expression pattern of eight Ptprd splice variants across brain regions and is modulated by neuronal activity. We identified both the intronic splicing enhancer region (ISE) for meB contributing to the spatiotemporal patterning of the AS and the neuronal activity–dependent intronic splicing silencer region for meB (ISS). Heterozygous deletion of the ISE in mice led to a decreased meB selection rate by ~25% with unaltered total amount of PTPRD protein and caused severe sensory, motor, social, and emotional behavioral abnormalities but no obvious changes in learning and memory, while heterozygous Ptprd knockout mice with unaltered meB selection rate and ~50% decrease in total PTPRD protein showed much fewer behavioral abnormalities. Interestingly, deletion of the ISS for meB caused selective impairments in motor learning and fear memory. Our findings demonstrate the spatiotemporal and activity-dependent AS code for Ptprd meB plays a crucial role in proper behavioral development.